Voting with public information - Shuo Liu (University of Zurich, Department of Economics, 2015)
We study the effect of public information on collective decision-making in a committee with members of both common and conflicting interests. We show that the set of preferences that allow for the existence of an informative voting equilibrium can be heavily restricted by the presence of a public signal, regardless of the size of the committee and the choice of the voting threshold value. What's worse, the presence of the public information introduces an inefficient equilibrium which robustly exists across different voting rules. To mitigate the harmful effect of the public information, we propose to use a class of more flexible voting rules, whose threshold values depend on both the precision and the realization of the public signal, that may restore the informative voting equilibrium. In particular, in a standard setting with common interest agents, the contingent voting rule that we construct not only always restores the informative voting equilibrium but also achieves full informational efficiency.
Keywords: D72; D82; 330; strategic voting; collective decision-making; public information; committee design; optimal voting rule